2006
DOI: 10.1007/s10209-006-0025-0
|View full text |Cite
|
Sign up to set email alerts
|

Odd Job Jack described: a universal design approach to described video

Abstract: People who are blind or have low vision have only recently begun to enjoy greater access to television and video through a new technology, called descriptive video information (DVI). Two styles of DVI production for animated comedy content were compared. The first model used a conventional description style, and the second used a first person narrative style. In addition, the first person narrative style was produced by the original animation creation team. Results from blind participants show that using the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 5 publications
2
41
0
Order By: Relevance
“…As a result, and similar to the experience of museums, blind and low-vision theatregoers may not even be considered as a potential audience or valuable customer base. However, designing inclusion into a production from its conception as purported by universal design theory is relatively simple to accomplish and may result in a more inclusive experience for all audience members Fels, Udo, Ting et al 2006; Udo and Fels forthcoming a).…”
Section: Museum Touch Toursmentioning
confidence: 97%
See 1 more Smart Citation
“…As a result, and similar to the experience of museums, blind and low-vision theatregoers may not even be considered as a potential audience or valuable customer base. However, designing inclusion into a production from its conception as purported by universal design theory is relatively simple to accomplish and may result in a more inclusive experience for all audience members Fels, Udo, Ting et al 2006; Udo and Fels forthcoming a).…”
Section: Museum Touch Toursmentioning
confidence: 97%
“…For example, new initiatives have been developed to assist individuals who are blind or have low-vision access live events. Audio description has become the most popular of these initiatives, generally as an adaptive process in which visually important events are verbally described and inserted in non-dialogue spaces Fels, Udo, Ting et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies concerning AD concentrated mainly on the entertainment function of audio-described programmes (Fels, Udo, Ting, Diamond, & Diamond, 2005 ;Udo & Fels, 2009 ). A number of projects focused on feature fi lms and theatre performances (Bourne & Jiménez Hurtado, 2007 ;Orero, 2007 ;.…”
Section: Audio Description In Educationmentioning
confidence: 99%
“…Recent studies have shown, however, that audiences respond positively to alternative versions of AD. Fels, Udo, Ting, J. E. Diamond and J. I. Diamond (2006) compared the reactions of The other AD script was called 'cinematic'. It intentionally contradicted the Ofcom guidelines by incorporating specific film terminology.…”
Section: Introductionmentioning
confidence: 99%